Analisis Tingkat Kepuasan Pengguna terhadap Sistem E-Learning Berbasis Mobile dengan Pendekatan Technology Acceptance Model - Zaydan Arka Mahendra; Keira Safira Nadhira; Elvano Rafiq Pradipta (Journal of Science and Technology: Alpha, 2026)
This study aims to analyze user satisfaction with a mobile-based e-learning system using the Technology Acceptance Model approach. The research employed a quantitative approach with an explanatory survey design. The respondents were active users of a mobile-based e-learning system in a higher education environment. Data were collected using a closed-ended questionnaire based on a five-point Likert scale measuring six main variables: perceived ease of use, perceived usefulness, attitude toward using, behavioral intention, actual use, and user satisfaction. A total of 186 valid responses were analyzed using descriptive statistics, validity testing, reliability testing, and multiple linear regression. The results show that user satisfaction was in the high category, with a mean score of 4.01. Perceived usefulness obtained the highest mean score of 4.18, followed by perceived ease of use at 4.12, behavioral intention at 4.05, attitude toward using at 3.96, and actual use at 3.88. The regression results indicate that all Technology Acceptance Model variables significantly influenced user satisfaction, with an R-square value of 0.672. Perceived usefulness was identified as the most dominant factor affecting user satisfaction. These findings indicate that the success of a mobile-based e-learning system is not only determined by the availability of the application, but also by perceived benefits, ease of use, positive attitudes, continuance intention, and actual usage experience. This study provides practical implications for educational institutions to improve feature quality, access speed, navigation, learning content quality, and technical support for mobile e-learning systems.